The Effect Of FFB Prices On The Welfare Of Oil Palm Farmers In Mentawak Village Merangin Regency - Elvina Safitri; Hera Hartati; Sri Utamingsih (Enrichment : Journal of Management, 2022)
This study aims to determine how far the influence of the price of Oil Palm FFB in Mentawak Village, Nalo Tantan District. The research was conducted at the price of fresh fruit bunches (FFB) of oil palm Rp. 1,200.00/kg. The method used is a quantitative research method with simple linear regression using the SPSS version 22 program. The results of this study the regression model obtained is Y=44,554+0,074 X. The regression model obtained at the price of oil palm FFB Rp. 1,200.00/kg is worth positive, so that it is said that the price of oil palm FFB and the welfare of oil palm farmers is positively related. This study suggests that related parties pay more attention to farmers and can provide guidance such as training/counseling to farmers so that they can make derivative products from oil palm plantations. Thus, it is hoped that the farmers will not only benefit from the sale of their agricultural/plantation products but also become entrepreneurs.